What European gynaecologists need to master: Consensus on medical expertise outcomes of pan-European postgraduate training in obstetrics & gynaecology. (September 2017) - van der Aa, Jessica E.; Tancredi, Annalisa; Goverde, Angelique J.; Velebil, Petr; Feyereisl, Jaroslav; Benedetto, Chiara; Teunissen, Pim W.; Scheele, Fedde
Abstract: Objective: European harmonisation of training standards in postgraduate medical education in Obstetrics and Gynaecology is needed because of the increasing mobility of medical specialists. Harmonisation of training will provide quality assurance of training and promote high quality care throughout Europe. Pan-European training standards should describe medical expertise outcomes that are required from the European gynaecologist. This paper reports on consensus development on the medical expertise outcomes of pan-European training in Obstetrics and Gynaecology. Study design: A Delphi procedure was performed amongst European gynaecologists and trainees in Obstetrics & Gynaecology, to develop consensus on outcomes of training. The consensus procedure consisted of two questionnaire rounds, followed by a consensus meeting. To ensure reasonability and feasibility for implementation of the training standards in Europe, implications of the outcomes were considered in a working group thereafter. We invited 142 gynaecologists and trainees in Obstetrics & Gynaecology for participation representing a wide range of European countries. They were selected through the European Board & College of Obstetrics and Gynaecology and the European Network of Trainees in Obstetrics & Gynaecology. Results: Sixty people participated in round 1 and 2 of the consensus procedure, 38 (63.3%) of whom were gynaecologists and 22 (36.7%) were trainees in Obstetrics & Gynaecology. Twenty-eight European countries were represented in this response. Round 3 of the consensus procedure was performed in a consensus meeting with six experts. Implications of the training outcomes were discussed in a working group meeting, to ensure reasonability and feasibility of the material for implementation in Europe. The entire consensus procedure resulted in a core content of training standards of 188 outcomes, categorised in ten topics. Conclusion: European consensus was developed regarding the medical expertise outcomes of pan-European training in Obstetrics and Gynaecology. The outcomes will be described in core trainings standards, aimed at harmonising training in Obstetrics and Gynaecology in Europe to promote high quality care.